Rietveld Texture Analysis for Metals Having Hexagonal Close‐Packed Phase by Using Time‐of‐Flight Neutron Diffraction at iMATERIA. Issue 4 (3rd July 2017) - Onuki, Yusuke; Hoshikawa, Akinori; Nishino, Soichiro; Sato, Shigeo; Ishigaki, Toru
Abstract : Texture is an important property especially for metallic materials having hexagonal close‐packed crystal structure. In order to understand the overall property or change in the microstructure of materials, neutron diffraction is a powerful tool of investigation. In this study, we attempt to measure the textures of Ti–6Al–4V (mass%) alloy by using a time‐of‐flight neutron diffractometer, iMATERIA. The results indicate that the texture measurement for the hexagonal phase is possible with the same method as for cubic metals. The texture of cubic β phase, whose volume fraction is several percent, can simultaneously be determined together with the hexagonal α phase. Abstract : Quantitative texture measurement/analysis for a HCP crystal is verified by using data from iMATERIA, time‐of‐flight‐neutron diffractometer at J‐PARC MLF, Japan. In the current study, textures of both HCP α and BCC β phases in Ti‐6 mass% Al‐4 mass% V are simultaneously determined by the Rietveld texture analysis using data acquired at a single neutron exposure.